Հայրենական մեծ պատերազմում զոհված հայ նկարիչներ - Մ. Ա. Կիրակոսյան (ՀՀ ԳԱԱ հրատ.)
Творчество погибших в Великой Отечественной войне художников Корюна Симоняна, Левона Тонаканяна, Андраника Маркосяна и Левона Тотовенца занимает достойную нишу в армянской живописи. The author analyzes the life and career of the artists Koryun Simonyan, Levon Tonakanyan, Andranik Markosyan and Levon Totovents, perished in the Great Patriotic War. They have occupied a worthy niche in the Armenian painting.
Keywords: History; World War II; D History; N Fine Arts; ND Painting